Investigating Maternal Perception of Control and Support in the Postpartum Period and Influencing Factors in Childbirth: A Multiple Linear Regression Analysis Model - Tuğba Yazici Topçu; Ruveyde Aydin; Songül Aktaş (Nursing Open)
ABSTRACT Aim This study aimed to assess the levels of maternal perception of control and support during birth and the factors influencing them in the postpartum period. Design A cross‐sectional design was employed. The STROBE checklist was used. Methods The study was conducted between July 2021 and March 2022 with 400 mothers who were in their first 2 months postpartum and lived in Türkiye. Data were collected online using a Maternal Descriptive Information Form and the Support and Control in Birth (SCIB) Questionnaire. Descriptive statistics, such as percentage, mean, standard deviation and multiple linear regression analysis, were employed for data evaluation. Results The mean score on the total SCIB was 92.4 ± 13.01. Vaginal birth and caesarean section accounted for 47.3% and 52.7% of the study group, respectively, with only 35% being assisted by a midwife. Variables of age, education level, number of pregnancies, mode of birth and health professionals assisting birth showed no significant effect on the total SCIB score (p > 0.05). Maternal satisfaction with birth scores, satisfaction with health professionals involved birth and fulfilled expectations from health professionals were positively associated with high SCIB scores (p < 0.05). Conclusion The level of SCIB in our study fell within a ‘moderate’ range, considering the lowest and highest scores on the scale. Notably, increased satisfaction with birth experience and healthcare professionals, positively influenced maternal perceptions of control and support during birth. In contrast, certain socio‐demographic and obstetric characteristics did not demonstrate a significant impact. To enhance the sense of support and control during childbirth, it is crucial to identify and fulfil the expectations of mothers from midwives and birth supportive care to ultimately elevate maternal satisfaction in the childbirth experience. Patient or Public Contribution None.